B Cell Subsets and Cellular Signatures and Disease Relapse in Lupus Nephritis - Yap, Desmond Y. H.; Yung, Susan; Lee, Paul; Yam, Irene Y. L.; Tam, Cheryl; Tang, Colin; Chan, Tak Mao (Frontiers in Immunology, 2020)
Introduction: Renal relapses adversely affect the long-term outcomes of patients with lupus nephritis (LN), but the pathogenic mechanisms remain elusive. B cell signatures of miR-148a, BACH1, BACH2 and PAX5 expression are relevant to the regulation of B lymphocyte homeostasis. It is unknown whether B cell signature is related to relapse of LN. Methods: We compared B lymphocyte subsets and cellular signatures during disease quiescence between LN patients with multiple relapses (MR, ≥3 LN relapses within 36 months) and those with no relapse (NR). Also, circulating B lymphocytes were isolated from treatment-naïve patient with active LN and treated with antagomir-148a in vitro to investigate the relationship between miR-148a, BACH1, BACH2 and PAX5. Results: MR patients (n=19), when compared with NR (n=14), showed significantly lower percentage of circulating naïve B cells and higher memory B cell-to-naïve B cell ratio. MR patients also showed higher miR-148a levels in sera and B cells, and lower BACH1, BACH2 and PAX5 expression in naïve and memory B cells. Antagomir-148a upregulated BACH1, BACH2 and PAX5 expression, and reduced B cell proliferation upon stimulation, in naïve and memory B cells isolated from treatment-naïve active LN patients. Conclusion: Altered B cell subsets and cellular signatures of miR-148a, BACH1, BACH2 and PAX5 may be associated with distinct patient phenotypes related to the risk of LN relapse.